Exploring the Health Conditions and Practices of Public School Teachers: A Phenomenological Study - Perez, Rexomar D.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
The teachers’ role in the teaching and learning process is vital. However, they can only be effective if they maintain their health and energy levels. Thus, this phenomenological inquiry intends to explore the health of public school teachers in Negros Occidental, Philippines. The data were gathered using an in-depth interview. Meanwhile, the recursive textual analysis guided by the three C's of Lichtman- Coding, Categorizing, and Conceptualizing was employed to analyse the data thematically. The findings show that teachers did not feel any pain nor weakness, slept well, had enough energy to do tasks, and were free from any diseases. Hence, health issues were managed accordingly. Likewise, teachers exemplified their practices in monitoring their weight, medical results, food intake, and feelings of oneself. Also, teachers shared that to be healthy is to think that you are healthy. Thus, eating healthy food, regular exercise, and enough fluid consumption are the most common health practices of teachers that helped alleviate their health status and self-confidence. In general, teachers emphasized considering one's physical conditions, focusing on things that make them healthy. Henceforth, individual assessment of health status differs. Nevertheless, regular practice of healthful behaviors can maintain or improve health.